The prognostic role of advanced hemodynamic variables in patients with left ventricular assist devices. Issue 3 (12th November 2022) - Kanelidis, Anthony J.; Siddiqi, Umar; Miller, Tamari; Belkin, Mark; Li, George; Smith, Bryan; Kalantari, Sara; Nguyen, Ann; Chung, Ben B.; Sarswat, Nitasha; Kim, Gene; Salerno, Christopher; et al.
Abstract: Background: Invasive hemodynamic variables obtained from right heart catheterization have been used for risk‐stratifying patients with advanced heart failure (HF). However, there is a paucity of data on the prognostic value of invasive hemodynamic variables in patients with left ventricular assist devices (LVAD). We hypothesized that cardiac power output (CPO), cardiac power efficiency (CPE), and left ventricular stroke work index (LVSWI) can serve as prognostic markers in patients with LVADs. Methods: Baseline hemodynamic data from patients who had LVAD ramp studies at our institution from 4/2014 to 7/2018 were prospectively collected, from which advanced hemodynamic variables (CPO, CPE, and LVSWI) were retrospectively analyzed. Univariate and multivariable analyses were performed for hemocompatibility‐related adverse events (HRAE), HF admissions, and mortality. Results: Ninety‐one participants (age 61 ± 11 years, 34% women, 40% Black or African American, and 38% ischemic cardiomyopathy) were analyzed. Low CPE was significantly associated with mortality (HR 2.42, 95% CI 1.02–5.74, p  = 0.045) in univariate analysis and Kaplan–Meier analysis ( p  = 0.04). Low LVSWI was significantly associated with mortality (HR 2.13, 95% CI 1.09–4.17, p  = 0.03) in univariate analysis and Kaplan–Meier analysis ( p  = 0.02). CPO was not associated with mortality. CPO, CPE, and LVSWI were not associated with HRAE or HF admissions. Conclusions: Advanced hemodynamic variables can serve as prognostic indicators for patients with LVADs. Low CPE and LVSWI are prognostic for higher mortality, but no variables were associated with HF admissions or HRAEs. Abstract : The use of advanced hemodynamic variables can serve as prognostic indicators for patients with left ventricular assist devices. Low cardiac power efficiency (CPE) and left ventricular stroke work index (LVSWI) are prognostic for higher mortality.